Bone Remodeling in Mandible of Wistar Rats with Diabetes Mellitus and Osteoporosis - Hendrijantini, Nike; Suisan, Yonatan Christian; Megantara, Rizko Wira Artha; Tumali, Bambang Agustono Satmoko; Kuntjoro, Mefina; Ari, Muhammad Dimas Aditya; Sitalaksmi, Ratri Maya; Hong, Guang (European Journal of Dentistry, 2022)
Objectives This study aimed to determine some of bone molecular expressions and its possible bone remodeling pathway between diabetes mellitus (DM) and osteoporosis model in the mandibular bone of Wistar rats.Materials and Methods Twenty-seven female Wistar rats were divided randomly into control and treatment groups. Treatment groups were injected with streptozotocin intraperitoneally to induce DM (P1) and underwent bilateral ovariectomy to generate osteoporosis (P2). All groups were terminated after 12 weeks. Immunohistochemical and hematoxylin–eosin staining were performed to determine the expression of Runt-related transcription factor 2 (RUNX2), Osterix, vascular endothelial growth factor (VEGF), receptor activator of nuclear factor κB ligand (RANKL), osteoprotegerin (OPG), tartrate-resistant acid phosphatase (TRAP), and observed the osteoblast and osteoclast. Statistical analysis was performed using one-way analysis of variance.Results The lowest mean of RUNX2 and VEGF expression was found in the P2 group. The lowest mean of Osterix expression was found in the P1 group. Both P1 and P2 groups of osteoblast/osteoclast ratio were decreased. There were no significant differences in the expression of TRAP between all groups; however, increased expression of RANKL/OPG ratio was only found in the P2 group.Conclusion DM and osteoporosis induce changes in the bone remodeling pathway which are represented by a decrease in osteoblast biomarkers and an increase in osteoclast biomarkers.
Keywords: diabetes mellitus; osteoporosis; bone remodeling; medicine